Characterisation of the thermal ageing effects on the mechanical properties when reusing polyamide 12 in the selective laser sintering process. Issue 4 (7th April 2022) - du Maire, P.; Sert, E.; Deckert, M.; Johlitz, M.; Öchsner, A.
Abstract: Additive manufacturing is one of the key technologies for the future production of complex and individualised components. One of the most challenging questions to minimize the production cost is the reuse of the powder leftover after the building process. This study investigates the influence on the mechanical properties when reusing the leftover powder out of the process chamber up to four times. Tensile test specimens are produced and investigated. The results show a decreasing in the ultimate tensile strength with repeated reuse of the leftover powder. After four times of reuse the strength increases again. This cannot be explained by the literature and has to be verified in further investigations. The investigations reveal a high mechanical anisotropy as the strength highly depends on the component orientation in the process chamber. The particle shape does not show any differences between virgin and aged powder under the scanning electron microscope. Abstract : Decrease of the tensile strength after reusing the leftover powder from the selective laser sintering process. This paper determines the effects on the mechanical properties when reusing thermal aged polyamide powder in the selective laser sintering process. Translation abstract: Die additive Fertigung zählt zu den Schlüsseltechnologien für die zukünftige Produktion komplexer und individualisierter Bauteile. Eine der größten Herausforderungen, um die Produktionskosten zu minimieren, ist die Wiederverwendung des nach dem Bauprozess übrig gebliebenen Pulvers. In dieser Studie wird der Einfluss auf die mechanischen Eigenschaften bei mehrmaliger Wiederverwendung des nicht aufgeschmolzenen Pulvers untersucht. Es werden Zugproben hergestellt und untersucht. Die Ergebnisse zeigen eine Abnahme der Zugfestigkeit bei wiederholter Wiederverwendung des Restpulvers. Nach viermaliger Wiederverwendung steigt die Festigkeit wieder an. Der Anstieg lässt sich nicht abschließend begründen und muss in weiteren Untersuchungen verifiziert werden. Die Untersuchungen zeigen eine hohe Anisotropie, da die Festigkeit stark von der Orientierung der Komponenten in der Prozesskammer abhängt. Unter dem Rasterelektronenmikroskop können keine Unterschiede zwischen Neupulver und thermisch belasteten Pulver festgestellt werden.